Modeling Mechanical Vibrations Using Matlab's Graphical User Interfacer (Agroindustria, Sociedad y Ambiente, 2022)
Quality management is all the processes that are carried out in a company to ensure optimal execution of its activities, including the maintenance of machinery. Mechanical vibrations play a very important role in all physical phenomena in which a body vibrates and therefore suffers changes around a point of equilibrium, even affecting the operation of machinery involved in industrial processes, therefore the modeling of vibrations will establish control and measurement mechanisms for preventive maintenance, from the estimation of the current and future state of the instruments. For the modelling of the vibrations in industrial processes, second order differential equations with constant coefficients have been used through the Runge-Kutta method. To facilitate the resolution of the equation system, a Graphical User Interface has been developed using the MATLAB program, which allows the modelling of the general problem of mechanical vibrations, Therefore, the objective of this research was to evaluate the use of a graphic user interface for the modeling of mechanical vibrations by solving second-order differential equations, using the Runge-Kutta method. The equation solving was applied to undamped vibrations, free damped vibrations, and forced vibrations, the applicability of the method was validated by an expert through the application of the Design Thinking tool, which allowed its validation through the application of a usability test. The results show that the developed Graphical User Interface is very useful for the identification, analysis and formulation of solutions on the problem of mechanical vibrations and preventive mechanical maintenance.
Keywords: Efficiency, industrial engineering, industrial machinery